Dietary l-arginine Supplementation Alleviates the Intestinal Injury and Modulates the Gut Microbiota in Broiler Chickens Challenged by Clostridium perfringens - Zhang, Beibei; Lv, Zengpeng; Li, Zhui; Wang, Weiwei; Li, Guang; Guo, Yuming (Frontiers in Microbiology, 2018)
Our previous reports suggested that dietary L-arginine supplementation attenuated gut injury of broiler chickens infected with Clostridium perfringens by enhancing intestinal immune responses, absorption and barrier function, but its effect on the gut microbiome of broiler chickens remains unclear. This experiment aimed at evaluating the effects of dietary L-arginine supplementation on the gut bacterial community composition and function of broiler chickens challenged with C. perfringens. In total, 105 one-day-old male Arbor Acres broiler chickens were assigned to three groups: Control (CTL), C. perfringens-challenged (CP), and C. perfringens-challenged and fed diet supplemented with 0.3% L-arginine (ARGCP) groups. The challenge led to macroscopic and histomorphological gut lesions, decreased villus height and increased the number of Observed species, Shannon, Chao1 and ACE indices of ileal microbiota, whereas L-arginine addition reversed these changes. Moreover, the three treatments harbored distinct microbial communities (ANOSIM, P < 0.05). At the genus level, 25 taxa (e.g., Nitrosomonas spp., Coxiella spp., Ruegeria spp., and Thauera spp.) were significantly more abundant in CP group than in CTL group (P < 0.05), whereas the levels of 23 genera of them were significantly decreased by L-arginine supplementation (P < 0.05). The abundances of only 3 genera were different between CTL and ARGCP groups (P < 0.05). At the species level, the challenge promoted the relative abundance of Nitrospira sp. enrichment culture clone M1-9, Bradyrhizobium elkanii, Nitrospira bacterium SG8-3 and Pseudomonas veronii, which was reversed by L-arginine supplementation (P < 0.05). Furthermore, the challenge decreased the levels of Lactobacillus gasseri (P < 0.05). Predictive functional profiling of microbial communities by PICRUSt showed that compared with CP group, ARGCP group had enriched pathways relating to membrane transport, replication and repair, translation and nucleotide metabolism and suppressed functions corresponding to amino acid and lipid metabolisms (P < 0.05). The relative abundances of KEGG pathways in L-arginine-fed broilers were almost equal to those of the controls. In conclusion, L-arginine alleviated the gut injury and normalized the ileal microbiota of C. perfringens-challenged chickens to resemble that of unchallenged controls in terms of microbial composition and functionality.